ANALISIS IMPLEMENTASI STRATEGI TERHADAP CAPAIAN KINERJA PERUSAHAAN - Arifin Arifin; Rusdi Abul Karim (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
This study aims to analyze the relationship Implementation Strategies Achievements Against Corporate Performance (Studies in PT. (Persero) Gorontalo Branch State Electricity Company). Targets to be achieved in this research is the improvement of the performance of PT. PLN Branch Gorontalo both financial and non-financial aspects as well as to bring transparency, accountability, responsibility and fairness of organizational management of SOEs, especially in PT. (Persero) Branch State Electricity Company Gorontalo. Basic data collection, namely through a list of questions that tested through the validity and reliability of each item contained questions on the questionnaire. The analytical method used is the path analysis (path analysis) by first converting the data into an interval scale ordinal scale. The object of this research is the implementation of the strategy and performance of the company. The first hypothesis testing results show that the simultaneous implementation of strategies which include good corporate governance (corporate governance) (X1), the structure or design organization (X2), strategic leadership (X3), and strategic control (X4) of 0.852 or 85, 2% and there are external variables that influence the performance of this variable of 0.148 or 14.8% eg management control systems and operational management. While testing the hypothesis that sub-variables of good corporate governance (corporate governance) (X1) partially significant effect on the achievement of corporate performance (Y) at the test level 0.05 or 5% of 42.5%; structure or design organization (X2) partially significant effect on the achievement of corporate performance (Y) at the test level 0.05 or 5% of 42.4%, strategic leadership (X3) partially significant effect on the achievement of corporate performance (Y) at test level 0.05 or 5% for 33.6% and strategic control (X4) partially significant effect on the achievement of corporate performance (Y) at test level 0.05 or 5% of 10.2%.